The EFFECT OF SPHERICAL GRIP ROM EXERCISE ON ELDERLY WITH STROKE AT RST BHAKTI WIRA TAMTAMA SEMARANG - Wilanti, Attina Rigil (NHM PRESS, 2024)
Background: Stroke patients need rehabilitation to minimize physical disabilities so they can carry out normal activities. One type of rehabilitation that can be given to stroke patients is range of motion exercises or what is often called Range of Motion (ROM). Spherical grip can be used as a treatment to prevent contractures and increase muscle strength in elderly people who suffer from stroke. Objective: to determine the effect of spherical grip ROM training on elderly people with stroke at RST Bhakti Wira Tamtama Semarang. Method: This type of research uses descriptive case studies. The subjects of this writing are elderly people with stroke, with a focus on studying the application of Spherical Grip ROM exercises in stroke patients. The instruments used include nursing care reports, standard operational procedures for Spherical grip. Data collection was carried out by interviews, observation and documentation. The process of analyzing and presenting data uses data collection techniques, data reduction, data presentation and conclusions. Results: The main nursing problem was physical mobility impairment. In this case study, both patients experienced weakness or hemiparase on one side of the body. Implementation of spherical grip therapy was carried out for 3 intervention days, once every day for 10-15 minutes. The results of the implementation of Spherical Grip ROM therapy showed that there was an increase in muscle strength in both respondents, which initially had a score of 2 to 3, namely being able to make movements against gravity but not being able to fight gravity. Conclusion: Spherical Grip ROM therapy can be used as an alternative therapy for stroke patients aimed at increasing muscle strength.